InStead: Demonstrating allyship through a REDress reconciliation project - Musayett, Mukwa; Smith, Patricia (Canadian Social Work Review / Revue canadienne de service social, 2024)
This article tells the story of how the personal truth and reconciliation journeys of an Indigenous professor and non-Indigenous (settler ally) master’s student coiled together after a university-based art exhibition. The exhibit, REDress Missing and Murdered Indigenous Women and Girls and Two-Spirit People (MMIWG2S), opened at Thompson Rivers University (TRU) Art Gallery in October 2021. Its purpose was to honour the Truth and Reconciliation Commission of Canada’s (2015) call to action #41. At the opening ceremony of the exhibit, Mukwa Musayett / Dr. Shelly Johnson gave a talk regarding murdered and missing Indigenous women, girls, and two-spirit people. The exhibit included a REDress pine needle sculpture by Patricia L. Smith. The sculpture and talk led to a joint discussion between us about the experiences that brought us to participate in the MMIWG2S exhibit at the same postsecondary institution. First, we developed a plan to write about this experience of Indigenous and settler allyship between a professor and a student. Second, we identified a proposed collaboration on an allyship project entitled InStead to further education, awareness and reconciliation regarding MMIWG2S with and between other postsecondary faculty, students, and community members.